WebMedia XX - Who We Are And What We Have Done In The Last Two Decades - Duarte, Alexandre; M. Júnio, Moacir L. de; Souza, Jansen; Brito, Alisson V. de; Trinta, Fernando A. M.; Viana, Ricardo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
In this paper we analyze the scientific articles published in 18 previous WebMedia editions, from 1995 to 2012, in order to provide a bird's eye view over the Brazilian Multimedia Community and to show how the research topics addressed in the WebMedia series of events have evolved over the time. We used Social Network Analysis techniques to identify research groups, clusters and topics on papers presented in the WebMedia events over the last two decades. The results showed that WebMedia has a multidisciplinary nature with a connected component of core authors that is evolving to include an increasing number of new authors every year, showing that the community is still evolving.